Effect of deposition temperature on polymorphous silicon thin films by PECVD: Role of hydrogen. (January 2016) - Hamui, L.; Monroy, B.M.; Kim, K.H.; López-Suárez, A.; Santoyo-Salazar, J.; López-López, M.; Roca i Cabarrocas, P.; Santana, G.
Abstract: Pm-Si:H which has improved optical and transport properties as well as stability compared to hydrogenated amorphous silicon is studied. In order to understand the effect of the growth temperature on pm-Si:H films, hydrogen bonding and stability were analyzed in this work. Samples grown at different temperatures were compared and a change on the films morphology and structure was observed. HRTEM images evidence nanocrystals with approximate size of 9 nm. A growth surface reorganization was observed at an almost constant deposition rate. Increasing the deposition temperature leads to a more ordered, compact and smooth structure of the pm-Si:H films. Hydrogen interaction with the growing surface is related to the deposition temperature, changing the growth of the amorphous matrix due to hydrogen surface diffusion into lower energy and more stable positions. The total hydrogen in the film is reduced as temperature increases and hydrogen becomes more tightly bonded, which changes in a non monotonous way how the nanocrystals are incorporated and their environment. The optoelectronic properties of the films are directly related to the incorporation of hydrogen and whether it is weakly or tightly bonded. A diminution of the optical gap of the pm-Si:H films in the range from 1.71 to 1.65 eV was observed with the increase of the deposition temperature in the range from 175 to 275 °C.